1998
DOI: 10.1002/hep.510270627
|View full text |Cite
|
Sign up to set email alerts
|

Porphyria cutanea tarda, hepatitis C, and HFE gene mutations in north america†

Abstract: In some, but not all countries, porphyria cutanea tarda (PCT) has been associated with chronic infection with the hepatitis C virus (HCV). Recently, PCT has also been associated with mutations in the HFE gene that are associated with HLA-linked hereditary hemochromatosis. Until now, few studies of these associations have been reported from North America. The aims of this study were: 1) to assess the prevalence of HCV infection and HFE mutations in North American patients with PCT; 2) to compare demographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
137
1
11

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(167 citation statements)
references
References 53 publications
18
137
1
11
Order By: Relevance
“…2 The second missense mutation, H63D, was caused by a C to G transversion at 187 nucleotides of the open reading frame. A role for genetic hemochromatosis in the pathogenesis of iron overload in PCT has been also suggested, 3 and high association of HFE and PCT has been reported in Italian 4 as well as in British patients. 5 Although HH is common in populations of Northern European origin, with frequency of 1 of 200 to 1 of 300, 6 it is rare in African, Asian, and Australian populations.…”
Section: C282y and H63d Mutations In The Hfe Gene Are Not Associatedmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The second missense mutation, H63D, was caused by a C to G transversion at 187 nucleotides of the open reading frame. A role for genetic hemochromatosis in the pathogenesis of iron overload in PCT has been also suggested, 3 and high association of HFE and PCT has been reported in Italian 4 as well as in British patients. 5 Although HH is common in populations of Northern European origin, with frequency of 1 of 200 to 1 of 300, 6 it is rare in African, Asian, and Australian populations.…”
Section: C282y and H63d Mutations In The Hfe Gene Are Not Associatedmentioning
confidence: 99%
“…Population studies to establish an association between the 2 principal HFE mutations 1,2 and sporadic porphyria cutanea tarda (SPCT) 3 have led to varying results. Roberts et al 4 found the C282Y mutation in 18 of 41 (44%) British patients with SPCT, 7 of whom (17%) were homozygous.…”
Section: C282y and H63d Mutations In The Hfe Gene Are Not Associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…66 These patients have additional benefit from phlebotomy, because lowering iron improves hepatic inflammation and response to interferon treatment. 67 There must be a predisposition for Urod deficiency, because most patients with hepatitis C do not develop PCT. 68 As PCT may be the first indication of an HCV infection, it is important to be searched in all patients.…”
Section: Triggerrring Factorsmentioning
confidence: 99%
“…1,5,6 Some individuals with chronic HCV develop a number of extrahepatic comorbidities, ranging from autoimmune manifestations to disorders such as diabetes. [7][8][9][10] A geographic gradient with respect to autoimmune manifestations in HCV may exist. For example, the presence of cryoglobulins and autoantibodies is largely a southern European phenomenon.…”
Section: Introductionmentioning
confidence: 99%